REKONSTRUKSI PENEGAKAN HUKUM TINDAK PIDANA KEKERASAN DALAM PERSPEKTIF KEADILAN RESTORATIF PASCA UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL DAN KITAB UNDANG-UNDANG HUKUM PIDANA NOMOR 1 TAHUN 2023 - Dadang Rachmat; Siti Humulhaer; Dede Agus Sodikin; Djamal Efendi; Ervawati (CV. Lafadz Jaya, 2026)
This study analyses the paradigm shift in the enforcement of criminal law relating to acts of violence in Indonesia following the enactment of Law No. 12 of 2022 on Sexual Violence Offences (UU TPKS) and the Criminal Code No. 1 of 2023 (New Criminal Code). Employing a normative legal research method with a conceptual and legislative approach, this study traces the evolution from a retributive paradigm towards restorative justice in the handling of criminal cases involving violence. The findings indicate that the integration of restorative justice into the Indonesian criminal justice system presents substantive challenges regarding the balance between victim protection and offender rehabilitation. The UU TPKS provides an explicit legal basis for the application of restorative justice through Article 23, which regulates the discontinuation of prosecution based on restorative justice, whilst the New KUHP strengthens victim protection through more comprehensive provisions on physical violence. However, practical implementation faces structural barriers in the form of limited capacity among law enforcement officials, resistance from patriarchal culture, and the absence of standard operating procedures. This study recommends policy reform through the development of standard operating procedures (SOPs) for restorative justice, the strengthening of independent mediation institutions, and the harmonisation of the Criminal Procedure Code (KUHAP) with the TPKS Law to realise a criminal justice system oriented towards recovery and reconciliation.